OTOMATISASI MANAJEMEN BANDWIDTH INTERNET DENGAN INTEGRASI METODE HTB DAN PCQ DI DESA BARON KABUPATEN GRESIK - Mohammad Syarifuz Zaim; Henni Endah Wahanani; Achmad Junaidi (STKIP PGRI Tulungagung, 2025)
PT Persada Data Multimedia is an Internet Service Provider (ISP) company that focuses on dedicated network management. Operating in Laren District, Lamongan Regency, PT Persada Data Multimedia expands its services and supports the development of information technology in East Java, including Baron Village, Gresik Regency. In Baron Village, PT Persada Data Multimedia serves about 90 customers. Along with the increase in the number of customers, the complexity of network traffic increases, so effective and efficient network management is required. The use of proper bandwidth management is very necessary, one of which is often used, namely the HTB (Hierarchical Token Bucket) and PCQ (Per Connection Queue) methods. Quality of Service (QoS) is used as a benchmark to define the characteristics of a network service related to the quality of the service by calculating the value of QoS parameters, namely: throughput, packet loss, delay, and jitter. The purpose of this research is to determine the QoS value generated by integrating both HTB and PCQ methods adaptively based on the bandwidth distributed in Baron Village, Gresik Regency. Based on the tests that have been carried out, the QoS analysis results indicate that integrating the HTB and PCQ methods produces satisfactory results, with an index value of 3.375 increasing from the previous value of 3.5 with a value difference of 0.125. This result is based on the average results of test results on 4 QoS parameters: throughput, packet loss, delay, and jitter.